A União Cultural Brasil-Estados Unidos e as políticas culturais - Boyd, Andrew Blake (2003)
The topic of this research paper is the implantation of the União Cultural Brasil- Estados Unidos, in Brazil, and its first few years of existence (1938-1951). The main focus is how this institution, from its creation through its first years of operation, progressed in the direction of the ideals and projects of American public and private groups. As a complement, it examines the participation of the União Cultural Brasil-Estados Unidos as an instrument of political diplomacy, mainly in cultural and educational aspects. Attention is centered on the school to examine it as an instrument of specific American policies and practices during the period chosen. In a major role, the Office of the Coordinator of Inter- American Affairs (OCIAA) and Brazilian and American intellectuals were involved in the propagation of American diplomacy, in general, and specifically in relation to the União Cultural Brasil-Estados Unidos. The text examines the first years of operation of the school, the founding of its English course, the composition of its courses and it accompanies the growth in the number of students. There are notes about the teaching methodology used by the school's American teachers and notes about the process of Americanization of immigrants in the U.S. that could have an influence on teaching methodology in Brazil. The text deals with the school's publications, in their various formats, and their influence on the lives of São Paulo's residents. It examines the publications in view of the organization's objectives, which were principally to foster common ground for Brasil and the United States in the realm of culture. There is a prologue and an epilogue to situate the school historically. The main sources come from the school itself, the Archives of the state of São Paulo and the Rockefeller Archives